School Buildings for the 21st Century: Some Features of New School Buildings in Iceland - Anna Kristín Sigurðardóttir (University of Ljubljana, 2011)
The aim of this study is to identify features of change in the recent design of school buildings in Iceland, and how they might affect teaching practices. Environmental and architectonic features characterising school buildings designed and built at the beginning of the 21st century are examined in light of challenges involving architecture, educational ideology, school policy and digital technology. The sample for the study consists of 20 schools located in four municipalities. Four of the school buildings were developed and built in this century, while the other 16 were designed in the 20th century. The design of all of the buildings was explored and reviewed by a multidisciplinary team. Data was collected by observations and photography at each school site, as well as by reviewing technical documents. The relationship between school design and school practices was studied through a questionnaire survey among all teachers, in order to find out whether teachers working in new environments differ from teachers in more traditional classroom settings. The results indicate a clear shift in the design of educational buildings. Flexibility, flow, openness and teamwork seem to guide recent school design. Clusters of classrooms or open spaces, transparent or movable boundaries, as well as shared spaces allowing for manifold interactions in flexible groups seem to be replacing traditional classrooms along confining corridors. Teachers working in open classroom environments collaborate more often than their counterparts. Teaching practices are also characterised by more opportunities for pupils to choose between tasks and enjoy more variation regarding group division and workspace arrangements.